ChemInform Abstract: A Facile Synthesis of 5‐Amino‐[1, 2, 3]triazolo[5, 1‐a]isoquinoline Derivatives Through Copper‐Catalyzed Cascade Reactions. Issue 17 (28th April 2014) - Chen, Yunfeng; Zhou, Shilei; Ma, Shan; Liu, Wenqian; Pan, Zhiquan; Shi, Xaodong
Abstract The first synthesis of title compounds (III) using a 1, 2, 3‐triazole building block is reported.